ETIKA PENELITIAN - Diman Suryanto (BRIN, 2005)
Science requires discipline and this in turn is governed by ethics. Scientific ethics is needed in the three aspects of scientific science, namely teaching, research, and the application of science. Research ethics must have started to be considered since the research was prepared and only ended after the results of the research were published. This description will briefly discuss research ethics at each stage of the research.